Biotic response to the environmental and climatic variability in a deep alpine lake (Lake Lugu) over the last 30 000 years in southwest China. (14th October 2019) - Wang, Qian; Hamilton, Paul B; Kattel, Giri; Kong, Lingyang
Abstract: Multiple biogeochemical variables in a sediment core from Lake Lugu in southwest China were studied to investigate the effects of regional environmental changes on the ecosystem. Subfossil Cladocera, together with diatom, pollen and geochemical records, were used to examine climate-induced changes in lake ecosystem since the Last Glacial Maximum (30 000–0 cal year BP). Consistency among these biological records indicates that the succession of zooplankton, algae and vegetation changed in response to direct and indirect climatic factors. Alterations in the nutrient supply mediated by climate-induced changes in vegetation and soil processes are likely responsible for the variability of cladocerans. During the Last Glacial Maximum, cladocerans were dominated by littoral taxa (e.g. Alona ), indicating an unproductive and oligotrophic lake system. A peak distribution in the pelagic Bosmina highlights the period of increased nutrient availability at 11 500 cal year BP. The ecological changes in Cladocera at 19 000 cal year BP and diatom communities at 18 000 cal year BP reveal independent and indirect responses to nutrient and light conditions induced by solar radiation and increased monsoon intensity across the study region. The palaeoecological archives from Lake Lugu sediments highlight a complex lake ecosystem influenced by both direct and indirect changes corresponding to climate changes and shifts in regional anthropogenic pressure over the last 30 000 years.